Bahan Ajar Pembelajaran Seni Drama dan Tari Sekolah Dasar Berbasis Kearifan Lokal Kabupaten Trenggalek - Yudha Julistiyana, Maria Ulfa (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2024)
Development of Teaching Materials for Elementary School Drama and Dance Arts Based on Local Wisdom in Trenggalek Regency, is an alternative for documenting all work resulting from the course process. Apart from that, it can be used as a PGSD student handbook to support the learning process. This teaching material has a special feature because the attached work is in the form of a video sourced from the local wisdom of Trenggalek Regency. The research implementation process was carried out in three stages, namely: 1) preliminary study and data collection, 2) planning and developing an initial draft, 3) validation test/review by validators. This is due to the limitations of researchers. The results of the review from language expert validators of the draft Teaching Material Book above obtained a score of 33 and after dividing the maximum number and percentage, the result was 82.5%. Meanwhile, the results of the review from the material validator got a score of 36 and after dividing the maximum number and giving a percentage, the result was 90%. The validation of these two aspects can be added up and divided by the maximum score, so that the total percentage of the draft Teaching Material Book is 82.25%. So that the draft Teaching Material Book for Elementary School Drama Arts and Dance Learning Courses can be declared valid in terms of appropriateness elements both in terms of language and material.